Pengaruh Perceived Quality, Perceived Pride, Terhadap Purchase Intention Gen Z pada Handphone Iphone di Aceh Barat - Rezatul Ilmina (INDO PUBLISHING, 2026)
This study aims to analyze the influence of Perceived Quality and Perceived Pride on Purchase Intention among iPhone users within Generation Z in West Aceh Regency. This research employs a quantitative method with a survey approach and involves 96 respondents as the research sample. The data were analyzed using multiple linear regression with the assistance of SPSS. Partially, the Perceived Quality variable obtained a t-value of 1.396 with a significance value of 0.166, which exceeds the significance threshold of > 0.10 (0.166 > 0.10), indicating that Perceived Quality does not have a significant effect on Purchase Intention. Meanwhile, the Perceived Pride variable recorded a t-value of 2.215 with a significance value of 0.029, which is below the 0.10 threshold, indicating that Perceived Pride has a positive and significant effect on Purchase Intention. Simultaneously, the F-test shows that both variables—Perceived Quality and Perceived Pride—jointly have a significant influence on Purchase Intention, as evidenced by the F-value of 7.678 with a significance value of 0.001. This finding highlights that the combination of product quality and a sense of pride associated with the brand provides a substantial and meaningful effect on consumers’ purchase intention. The Adjusted R² value of 0.126 indicates that these two variables explain 12.6% of the variance in Purchase Intention, while the remaining percentage is influenced by other factors outside this study. Thus, the study concludes that Perceived Pride is the most dominant factor influencing the Purchase Intention of Generation Z toward iPhone products, whereas Perceived Quality does not significantly affect purchase intention, despite showing a positive direction of influence